2013
DOI: 10.11113/jt.v64.2264
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Criteria and Adoption in Designing Business School’s Performance Management System

Abstract: This paper aims to present a principle to the business school institution that have slight familiarity in espousing benchmarking toward better performance. This is done since designing performance management system, espescially in defining key indicators is essential in achieving improvement process and better service. One approach to assist institution -notwithstanding with some pitfalls in it- is benchmarking. Moreover given the fact that industry best practice may never be found as it also relate with organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This wide-ranging approach looks at the processes by which results are accomplished (Ali Al-Khalifa, 2015;Ruby, 2013b;Scott, 2011). The type of benchmarking is not restricted to any institution (Rashed & Un, 2018), such as conducting benchmarking by visiting other schools once a year (Azis et al, 2013). The seventh type of benchmarking, functional benchmarking, involves comparing a single process (Vught et al, 2008) of an institution with another institution that is not a competitor but shares a standard function.…”
Section: Transdisciplinary Approachmentioning
confidence: 99%
“…This wide-ranging approach looks at the processes by which results are accomplished (Ali Al-Khalifa, 2015;Ruby, 2013b;Scott, 2011). The type of benchmarking is not restricted to any institution (Rashed & Un, 2018), such as conducting benchmarking by visiting other schools once a year (Azis et al, 2013). The seventh type of benchmarking, functional benchmarking, involves comparing a single process (Vught et al, 2008) of an institution with another institution that is not a competitor but shares a standard function.…”
Section: Transdisciplinary Approachmentioning
confidence: 99%
“…Several common problems often occured for designing layout for small factory, i.e. difficulties in locating the facilities (e.g., machines, departments) in a plant (Chikwendu & Okechukwu, 2016;Drira, Pierreval, & Hajri-Gabouj, 2007) ineffective material flows (Sharma, Singh, & Singhal, 2013) unflexible layout as difficult and slow in changing the production type (De Carlo, Arleo, Borgia, & Tucci, 2013) critical and complex task due to the increasing demands (Azise, Simatupang, Wibisono, & Basri, 2013;Benabes, Poirson, & Bennis, 2013) and hard modules of unequal dimensions in open space (Tasadduq, Imam, & Ahmad, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore those skills are needed to become an effective employees and effective leaders in their field in the future. 8 9 However, based on real situation in Indonesia, the institution of higher education is facing lots of obstacles in graduating student with those above characteristics or skills, due to standards incongruity; 10 11 various frameworks; blurred vision, strategies, and incompact fundamental foundation in managing institution performance; 12 13 and the failures of self evaluation and fuzziness of benchmarking processes, [14][15][16][17][18][19] likewise these issues has been on solemn agenda for last twenty years. 20 Furthermore, in line with it, although quality assurance has long been considered as one of main pillars for higher education development in four ASEAN countries, i.e., Indonesia, Malaysia, Philippines, and Thailand, the level of quality development among countries in this region is still quite diverse.…”
Section: Introductionmentioning
confidence: 99%
“…27 28 In addition, the existing performance standards despite of their relative benefits also have limitations. Several identified limitations are: (1) Override the existing system; 29 (2) Neglect the contextuality externally or internally; (3) Not equipped with guidance for benchmarking processes; 17 (4) No formulation for improvement recommendations for each poor performance. Moreover, it takes a systemic perspective on managing improvement and critically review dominant approaches to quality in higher education, and suggested to shift the quality activities focus from accountability and control to improvement.…”
Section: Introductionmentioning
confidence: 99%